Science Students’ Attitudes Towards the Use of Indigenous Language in Understanding Visual Representations - Moleboheng Ramulumo (Universitas Negeri Semarang, 2023)
This study aimed to investigate the attitudes of science students toward the utilization of their indigenous language in comprehending visual representations. A mixed-methods approach was employed to delve into students' perspectives, preferences, and beliefs regarding the medium of instruction in science education, with a specific emphasis on the role played by indigenous languages in the interpretation of visual representations. The study utilized a sequential explanatory research design, initially collecting and analyzing quantitative data, followed by qualitative data to augment the comprehension of the quantitative findings. The findings indicated a marked preference among students for employing English as the medium of instruction in science education, driven by its perceived global significance and potential advantages in accessing scientific resources and opportunities. Furthermore, students who had not been exposed to science education in their indigenous language exhibited negative attitudes toward its utilization. They also repudiated the notion that acquiring science knowledge in their indigenous language would enhance their ability to interpret visual representations effectively. These findings bear implications for the indigenization of curricula and underscore the significance of taking into account students' language preferences and attitudes in the context of science education. Future research should delve further into language choices in various educational settings and refine research instruments to enhance measurement precision. Educators and policymakers would be well-advised to consider students' language preferences to create inclusive and culturally responsive learning environments. This approach provides support to students in enhancing their proficiency in the selected language of instruction.